Produtividade e sólidos solúveis da melancia irrigada em função de doses de nitrogênio - Nowaki, Rodrigo Hiyoshi Dalmazzo [UNESP] (2014)
Nitrogen (N) is the second most accumulated nutrient by watermelon, with great influence on yield and fruit quality. The recommended range in the literature for the crop is large, mainly due to the diversity of climate, soil and crop management. Based on the foregoing, the work was developed with the objective of verifying the dose of N that maximizes productivity and total soluble solids hybrid Top Gun. The experiment was conducted in the field, at UNESP, Jaboticabal, SP, Brazil, with sowing on 29/08/2013 in Eutrofic Red Latossol. The experimental design was randomized blocks with six treatments, corresponding to N rates (0, 50, 100, 150, 200 and 250 kg ha-1) and four replications. Was used for drip irrigation and fertilization planting of coverage and system have been manually track and 10 cm from the plants. We observed significant effects of N content in nitrate-N in the soil, leaf N content, number of total and marketable fruit, total and marketable (PC) productivity, and fruit weight. The dose that achieved the greatest PC (34.96 t ha-1) was 184 kg ha-1 of N. There was no significant effect of N levels on soluble solids, with an average content of 10.7%